Surface characterization and electrochemical properties of PbO2/SnO2 composite anodes for electrocatalytic oxidation of m-nitrophenol. (1st March 2020) - Wang, Weiyi; Duan, Xiaoyue; Sui, Xinyu; Wang, Qian; Xu, Feng; Chang, Limin
Abstract: In this study, three kinds of SnO2 particles were synthesized by hydrothermal treatment with the assistance of three different surfactants of cetyl trimethyl ammonium bromide (CTAB), sodium dodecyl benzene sulfonate (SDBS) and sodium dodecyl sulfate (SDS). The synthesized SnO2 -CTAB, SnO2 -SDBS and SnO2 -SDS microparticles were successfully doped into β-PbO2 film of PbO2 electrode through composite electrodeposition technology to obtain PbO2 /SnO2 -CTAB, PbO2 /SnO2 -SDBS and PbO2 /SnO2 -SDS electrodes. Physical characterizations, electrochemical measurements and electrocatalytic oxidation of m -nitrophenol ( m -NP) were conducted to explore the electrocatalytic activity of prepared electrodes. The results showed that doping SnO2 was favorable to improve electro-catalytic activity of PbO2 electrode, which was attributed to that the SnO2 particles in β-PbO2 films improved the active sites on the surface, oxygen evolution potential and OH radicals generation rate of the electrodes. The experimental results also revealed that the PbO2 /SnO2 -CTAB was most efficient in three PbO2 /SnO2 electrodes due to the higher zeta potential, smaller particle size and higher specific surface area of SnO2 -CTAB than those of SnO2 -SDBS and SnO2 -SDS. Besides, the accelerated lifetime test shows that the PbO2 /SnO2 -CTAB electrode possessed longer service lifetime than PbO2 /SnO2 -SDBS, PbO2 /SnO2 -SDS and pristine PbO2 electrodes. Overall, the PbO2 /SnO2 -CTAB electrode is promising for environmental remediation. Graphical abstract: Image 1 Highlights: Three types of surfactant were used to assist the synthesis of SnO2 particles. PbO2 /SnO2 composite anode was fabricated using composite electrodeposition. PbO2 /SnO2 -CTAB showed optimum activity due to its higher OEP and more active sites.